THE NEODYMIUM ISOTOPIC COMPOSITIONS AND RARE EARTH PATTERNS IN HIGHLY DEPLETED ULTRAMAFIC ROCKS - Sharma M.; Wasserburg G.J. (My University, 1996)
A large number of terrestrial and extraterrestrial reservoirs are sampled by ultradepleted rocks containing mainly olivine and orthopyroxene. However, very few attempts have been made to determine the REE contents and neodymium isotopic composition of such samples due to substantial analytical problems in handling large sample volumes. We describe a chemical separation technique with high chemical yield and low contamination suitable for extraction of REEs from depleted ultramafic rocks. After sample dissolution, we use the Fe present in the rock for coprecipitation of REEs while keeping Mg, the dominant major element in an ultramafic rock, in solution. This technique reduces the effective sample size by an order of magnitude, thus permitting the use of existing column techniques to separate the lanthanides. Utilizing this procedure, eight harzburgites and a dunite, associated with the mantle sections of ophiolite complexes, were analyzed for REE and neodymium isotopic composition. The results show the LREE concentrations varying from sub parts per billion to less than 10 ppb; the Yb concentrations representing the HREEs vary from 1 to 70 ppb. The rocks have values ranging from −0.45 to +3.4 and ϵNd(0) values varying from −12.5 to +47.5. The ultramafic rocks can be classified into two groups using their initial ϵNd(t) values. The samples with ϵNd(t) > +7 are derived from depleted MORB mantle and show extreme LREE depletion and HREE enrichment with no hint of a U-shaped REE pattern. However, samples with ϵNd(t) < +7 yield REE patterns that are either U-shaped or flatten towards the LREE end are interpreted as having been contaminated by continental crust. We conclude that the U-shaped REE patterns found in many harzburgites associated with mantle sections of ophiolite complexes are the result of crustal contamination and not the consequence of peculiar fractionation during melting. The HREE depletion shown by the samples with ϵNd(t) > +7 can be modeled with equilibrium fractional melting. However, the observed ratios are several orders of magnitude higher than predicted by the melting model. We suggest that the high ratios in the ultradepleted samples may be a result of refertilization by basaltic melts. The chemical procedure developed in this paper permits a full exploration of ultradepleted rocks from the upper mantle as well as some classes of meteorites that are highly depleted.